Partner selection in market-driven strategic alliances - Saul Klein; Chekitan Dev (South African Journal of Business Management, 1997)
How should one select a strategic alliance partner? An answer to this question is provided by extending the literature on symbiotic marketing and focussing attention on market-driven strategic alliances. Such alliances are defined as long-term inter-firm co-operative relationships that add value for the customer. Value is created by providing the advantages of multiple choice purchase options coupled with the convenience of seamless, one-stop-shopping. This means paying attention to customers and competitors in selecting alliance partners. Market-driven strategic alliances are posited to be more successful when usage and firm complementarity levels are correctly matched with the alliance strategy being pursued.
Keywords: 650